Effect of SiO2 Nanoparticles Addition on the Flexural Strength of Repaired Acrylic Denture Base - Gad, Mohammed Moustafa Ahmed; Abualsaud, Reem; Al-Thobity, Ahmad M.; Almaskin, Danah F.; AlZaher, Zahra A.; Abushowmi, Tahani H.; Qaw, Masoumah S.; Akhtar, Sultan; Al-Harbi, Fahad A. (European Journal of Dentistry, 2020)
Objective The objective of this study was to evaluate the effect of nano-SiO2 addition on the flexural strength (FS) of repaired acrylic denture base.Materials and Methods Heat-polymerized acrylic resin specimens were fabricated in dimensions of (65 × 10 × 2.5 ± 0.1 mm3 ) and then sectioned and prepared, creating repair gap with butt (90 degrees) and bevel (45 degrees) repair surface designs forming two main groups according to joint design. Further subdivision was done into four groups (n = 10) according to nano-SiO2 concentration: one unmodified group and three modified groups (0.25, 0.5, and 0.75 wt %) in the autopolymerized repair resin. Each pair of a specimen was assembled in a mold and repaired according to manufacturer’s recommendations.Statistical Analysis Three-point bending test was done to measure FS, followed by scanning electron microscope (SEM) examination for fracture surface analysis. Data were analyzed using ANOVA and Tukey’s post hoc test (α = 0.05).Results The addition of nano-SiO2 significantly improved FS of repaired acrylic resin in comparison to the unmodified group (p ˂ 0.05). For butt joint, significant differences between nano-SiO2 reinforced groups were noticed (p ˂ 0.05), while reinforced beveled groups did not differ significantly (p ˃ 0.05). Bevel design remarkably increased FS compared with butt design per respective filler concentration. From the SEM images, improved FS was presented with a homogeneous distribution of nano-SiO2 within polymethyl methacrylate.Conclusion Nano-SiO2 addition to repair resin and 45 degree-beveled repair surface increased FS of repaired acrylic resin.
Keywords: denture repair; flexural strength; reinforcement; SiO2 nanoparticles